2022
DOI: 10.1371/journal.pntd.0010432
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological factors and tick density affect the dynamics of SFTS in jiangsu province, China

Abstract: Background This study aimed to explore whether the transmission routes of severe fever with thrombocytopenia syndrome (SFTS) will be affected by tick density and meteorological factors, and to explore the factors that affect the transmission of SFTS. We used the transmission dynamics model to calculate the transmission rate coefficients of different transmission routes of SFTS, and used the generalized additive model to uncover how meteorological factors and tick density affect the spread of SFTS. Methods In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Ticks, especially the H. longicornis, which had a higher density and wider distribution, were suggested to be the primary vector of SFTSV in China in recent years (1)(2)(3)(4). Research found that the tick density was one of the important factors affecting the occurrence of SFTS, and a high tick density reminded a higher exposure risk to SFTS (24,25). Zhejiang Province has always been the natural epidemic focus of SFTS (26).…”
Section: Discussionmentioning
confidence: 99%
“…Ticks, especially the H. longicornis, which had a higher density and wider distribution, were suggested to be the primary vector of SFTSV in China in recent years (1)(2)(3)(4). Research found that the tick density was one of the important factors affecting the occurrence of SFTS, and a high tick density reminded a higher exposure risk to SFTS (24,25). Zhejiang Province has always been the natural epidemic focus of SFTS (26).…”
Section: Discussionmentioning
confidence: 99%
“…Hurricanes reduce the incidence of SFTS in the short term, but have little effect in the long term. The most effective intervention to reduce the incidence of SFTS is to reduce population exposure to high-risk environments [ 15 ].…”
Section: Vector and Disease Transmissionmentioning
confidence: 99%
“…Previous studies have mainly focused on multivariate analysis methods to predict the incidence of SFTS. These studies analyzed various environmental, meteorological, and social factors, among others, to identify incidence-related risk factors and establish prediction models based on these factors ( Cho et al., 2021 ; Deng et al., 2022 ; Ding et al., 2014 ; Sun et al., 2018 , 2021 ; Wu et al., 2020 ). However, few studies have reported models for prediction of SFTS incidence just based on the historical incidence data, which may be more convenient and practical.…”
Section: Introductionmentioning
confidence: 99%